PENGARUH DAYA DUKUNG LAHAN DAN PERTUMBUHAN SEKTOR PERTANIAN TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN DAN KOTA DI PROVINSI ACEH - Hijri Juliansyah; Zubaidah Zubaidah (LPPM Universitas Malikussaleh - Indonesia, 2023)
This study aims to analyze the effect of land carrying capacity and agricultural sektor growth on economic growth in districts and cities in Aceh province. The data used in this study is panel data which consists of combining time series data and cross section data. The study was conducted in 23 provinces during 2011 to 2020. The data analysis method used was panel data regression analysis. Based on the model selection technique, the best model in this study is the fixed effect model. The results of the study partially that the carrying capacity of land has a negative and significant effect on economic growth in districts/cities in Aceh Province. The growth of the agricultural sektor has a positive and significant impact on economic growth in districts/cities in Aceh Province. Simultaneously, the carrying capacity of land and the growth of the agricultural sektor have a positive and significant impact on economic growth in districts/cities in Aceh Province.